Analysis of Tank Cleaning Implementation Using Crude Oil Washing on MT. Swordfish - ISKANDAR (PIP Makassar, 2026)
The implementation of Crude Oil Washing (COW) in the tank cleaning process on board the MT Swordfish still faces various technical and operational challenges, even though this method is considered more effective and environmentally friendly because it uses crude oil as a cleaning medium. This study aims to analyze the obstacles that arise in the implementation of COW and evaluate the efforts made to overcome these obstacles. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation techniques. The results of the study show that the implementation of COW faces several major obstacles, both technical and non-technical. Technically, the problems found include leaks in the COW pipe due to corrosion, disturbances in the Butterworth automatic system, and rust accumulation on the purging pipe and manhole components. Non-technical obstacles included the crew's limited understanding of COW procedures and work fatigue caused by insufficient personnel. To overcome these problems, various efforts were made, including equipment repairs and routine maintenance, improving the crew's understanding through briefing activities, and adjusting the task distribution system. Based on these findings, it can be concluded that the success of COW implementation is highly dependent on the condition of the equipment and the competence of the crew. Therefore, planned maintenance and continuous training are needed to improve efficiency, safety, and environmental sustainability in tank cleaning activities.